Making Use of Motivational Theories in Understanding Washback from Low- Stakess Test - Levita Dwinaya (Jurnal Sastra - Studi Ilmiah Sastra, 2019)
Washback is widely believed as common to happen in high-stakes test as this type of test impacts students’ life and future. Therefore, there is less concern on the type of washback which is generated from low-stakes test as it is believed that this type of test has no or less importance in students’ life and future. However, the hypothesis needs further investigation as test, no matter how low its stakes is, to certain extent influence students’ perception toward their learning. Therefore this article presents confirmatory study on whether washback is only generated by high-stakes test using three theories of motivation suggested by Watanabe (2006). The study used survey in form of questioner as the method of collecting data. The data were computed using SPSS and then analyzed using three theories of motivation. The result shows that using attributive theory of motivation, students tend to have internal motivation, using motivational theory of flow, students are motivated by the difficulty level of test being administered, while using functional autonomy of motives, students tend to be motivated to learn English by test. This indicates that washback effect generated by low-stakes test to students’ motivation was present in the context being investigated.